Dreams, Interests, Aspirations - Theodore R. Sizer (Journal of Research in Rural Education, 1996)
Aspirations have been part of American educational rhetoric for over 300 years. People here sought learning to give them courage, to help their children adhere to the old ways, to pave a road to collective and personal betterment.